Sikap Over Proteksi Orang Tua Dan Kematangan Sosial Anak - Uswatun Hasanah (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2016)
This study aims to find the relationship over protective attitude of parents with children early childhood social maturity. Over protection as independent variables and the dependent variable is the social maturity of the child. Subjects in the study were all students of early childhood education. totaling 40 children. Data were analyzed with statistical techniques Produc Moment. Analysis results obtained index value correlation r xy - 0.334; P = 0.033 (P <0.05), which means there is a significant negative relationship between Attitude Over Protection Parents with Children's Social Maturity. Data collection methods used in this study was a questionnaire to measure the scale of parenting Over protection used scale dikembangankan by the researchers themselves, Average to measure using the Children's Social Maturity The Vineland Social Maturity Scale. The conclusion is that there is a significant relationship between Parenting Over Child Social Protection at Maturity.